Recent Host Modulation Therapy: A Mini Review (Global Journal of Medical Research, 2021)
Periodontitis is one of the most ubiquitous diseases and is characterized by the destruction of connective tissue and dental bone support following an inflammatory host response secondary to infection by periodontal bacteria 1 The first clinical manifestation of periodontal disease is the appearance of periodontal pockets which offer a favorable niche for bacterial colonization It can be diagnosed by clinical examination with periodontal probe to determine pocket depths in combination with X-ray imaging using microbiological techniques for a precise analysis of the infectious agents 2 According to current concepts of the multifactorial etiology of periodontal disease it is caused by the interaction among single or multiple microbial agents a host with some degree of susceptibility and environmental factors with an influence on both Although a single model of the etiopathogeny of periodontal disease has yet to be validated it is broadly accepted that periodontal disease results from action of the bacterial biofilm on the periodontium of the susceptible individual Bacteria are able to survive and grow in the complex ecosystem of this biofilm because of their production of virulence factors These factors also confer a greater resistance to host defense mechanisms i e they increase the capacity of the bacteria to overcome the inflammatory reaction and immune response to antigen presentation 3